Symbolism In Ron Howard's Angels And Demons Movie (2009):A Semiotic Approach - NURJANNAH, NURJANNAH (2012)
The major problem of the study is how symbolism is reflected in Angels and Demons movie by Ron Howard. The objective of this study is to analyze the movie based on its structural elements and analyze the movie based on the semiotic approach. In Analyzing Angels and demons movie, the writer uses qualitative method and semiotic approach. The data source consists of primary data and secondary data sources. Primary data source is the Angels and demons movie directed by Ron Howard released in 2009. While secondary data source are other materials taken from books, journals and internet related to study. Both data collected trough library research and analyzed by descriptive analysis. The study comes to the following conclusion. Firstly, based on the structural analysis, it is evident that in this movie, the director is saying that "angels and demons are symbols of good and evil behavior of individuals in the society". Secondly, based on the semiotic analysis, it is apparent that in this movie, the director want to makes the audience realize that the war of good against evil is an everlasting war that everybody should fight in all ages.